The Risk Factor of Leprosy and The Care Process of Patient with Leprosy in Mahengetang Island of Sangihe: Qualitative Study - Yeanneke Tinungki; Detty Jeane Kalengkongan (Universitas Teuku Umar, 2021)
Leprosy is a chronic disease caused by Mycobacterium Leprae and can cause disability. Leprosy is a contagious disease from a medical perspective and extends social, economic, cultural, and social resilience issues. Mahengetang Island is one of the small islands in the Tatoareng District, Sangihe Islands Regency, with the highest leprosy cases in North Sulawesi Province. The research objective was to determine the risk factors for Leprosy and Care of leprosy patients in Mahengetang Tatoareng Island, Sangihe. The research method is a qualitative design with 13 informants who were interviewed. The participants are leprosy patients who undergo treatment and leprosy treatment which health workers supervise on Mahengetang Island. The research has been on for three months, from July to October 2020. The result showed that the risk factors for Leprosy were white spots (P1, P3, P5, P6), tasteless and cramps (P1, P2, P5, P10), thickened blackish skin (P2, P3, P4, P10, P12), itching and redness all over the body (P8). The result of research about leprosy patients are showed that one Participant took medication for six months (P1), seven participants took medication for one year, and five participants took the drug once. The conclusion is that the risk factors for Leprosy are white patches on the skin, tasteless and cramps, thickened black skin, itching, and redness all over the body. The care of Leprosy patients showed that all participants took Rifampicin with different periods depending on leprosy classification.